Propuesta de Inversión para la reactivación empresarial de la Estación de Servicios “Guadalupe” en el Cantón Saraguro – Provincia de Loja - Jaramillo Japa, Francisco Alexander (2016)
This project has been performed in order to determine whether the "INVESTMENT PROPOSAL FOR THE BUSINESS RECOVERY SERVICES STATION" GUADALUPE "IN CANTON SARAGURO. - Loja province", listed as a topic of this thesis has or infeasibility for such reopening, work in order to bring it to reality, the project has its place of implantation since in the town of Saraguro there is great discontent not to have sufficient and permanent supply of fuel, power supply this product to vehicles already exist in the canton vehicles traveling on the Panamerican Highway Loja - Cuenca. One of the main objectives is the general course of this work is to develop an investment project for the resumption of operations of the Service Station (station) "GUADALUPE" in the canton of Saraguro, Loja province., in order to check whether it is advisable to reactivate the functions of the company, therefore it has established specific objectives that give a clearer picture of what will be the possible outcome being the first to perform a market study to provide meet supply and demand exists, make a technical study to determine the optimal size of the plant, macro and micro location, project engineering and its installed and used capacity, and the instruments used in it, develop an organizational study which allows to observe how their departmental distribution, legal framework, manual functions and hierarchical level that you will have the company, and finally execute a financial study to determine the profitability of the business it is going to have reactivation of this station services and recovery time of investment. Once the financial study it was possible to determine that the initial investment of the company will be $ 309.172,48; a sum of net inflow of $ 638.072,94, providing equilibrium point 46.067glns determined in units or gallon of fuel sold and $ 267.989,02 for the first year a NPV of $ 123.286,69 and an IRR of 23,56%. The payback period of the investment will 3 years 8 meses 0 days, with a benefit / cost equal to $ 1.15; This result allowed to know the sensitivity of the project by the increase in the costs being 3.67%, which indicates whether the project is sensitive to this increase, while in declining revenue they can get up to 2,44%, giving a sensitivity of 0.99 and this positive result for the revival of that gas station. These calculations show a positive result, and that the project would be executed, considering that this project can increase its useful life so as to generate more profit for shareholders of the company.